Talus Fractures and Concomitant Injuries Patterns. Issue 4 (16th October 2019) - Ibrahim, Ishaq; Ye, Michael; Smith, Jeremy; Kwon, John Y.; Miller, Christopher P.
Category: Trauma Introduction/Purpose: Fractures of the talus are rare, but serious injuries to the hindfoot associated with high-energy mechanisms in often polytraumatized patients. The collective knowledge regarding talus injuries is lacking in many regards. Limited effort has been previously made to identify and characterize associated injuries ordinarily occurring in conjunction with fractures of the talus. The purpose of the current study was to [1] determine what associated injuries occur in high incidence in patients presenting with major fractures of the talus, and to [2] identify clinical injury patterns that warrant special attention in patients presenting with talus fractures. Methods: A retrospective review was conducted for patients with talar body or neck fractures at three level-1 academic trauma centers in Boston, MA between June 1, 2004 and June 30, 2018. Patient charts were reviewed for demographic details, injury mechanism, open versus closed injury status, and all associated orthopaedic and non-orthopaedic injuries identified during the initial patient encounter and hospitalization. Results: 253 patients met criteria for inclusion. The final study population included 158 (61%) talar neck fractures, 82 (32%) body fractures, and 18 (7%) head fractures. Falls from height, MVC/MCC, low energy falls and sports injuries were the most common mechanisms of injury in declining order. 64% of patients presenting with a talus fracture had at least one other concomitant injury. The table demonstrates the breakdown of associated injuries rates by body area. Conclusion: Talus fractures are commonly associated with injuries to different anatomic sites and systems. Trauma to the ipsilateral foot is most common necessitating complete imaging of the foot and ankle in all patients presenting with talus fractures. Trauma to the chest, abdomen, and pelvis occurred most commonly following motor vehicle trauma. Talar fractures and lumbar spine injuries was also observed frequently and underscores the importance of lumbar spine evaluation in patients presenting with major talus fractures, particularly those occurring after falls from height. This study presents valuable information to surgeons when evaluating and assessing injured patients to optimize care for patients.